Perceived Environmental Knowledge and Ease of Use: Keys to Increasing Purchase Intention of Sustainable Packaging - Adrianus Ketmoen; Engelbertus G. Ch. Watu; Apryanus Fallo; Lopes Amaral, Maria Augustin; Anggelina Delviana Klau (Universitas Negeri Semarang, 2025)
In the modern era, environmental issues have become a global concern due to the rising impacts of pollution and climate change. One solution is sustainable packaging to reduce waste and environmental damage. This study examines the relationship between environmental awareness, perceived environmental knowledge, perceived ease of use, and purchase intention, with trust in sustainable packaging as a mediating variable. The novelty lies in adding trust in sustainable packaging and utilizing local potential, namely lontar materials, as eco-friendly alternatives to recycled cloth, paper, and plastic. Using the Theory of Planned Behavior, a quantitative approach, and purposive sampling, the study collected 192 samples, with 170 valid responses. Results show that purchase intention is influenced by trust in sustainable packaging, environmental awareness, environmental knowledge, and ease of use. Trust is shaped by environmental awareness, environmental knowledge, and ease of use. Trust mediates the effect of environmental knowledge and ease of use on purchase intention but does not mediate the effect of environmental awareness. These findings are valuable for producers using lontar-based packaging, suggesting they target environmentally conscious consumers who value knowledge and usability.